Аналіз та визначення актуальності створення стрілецьких тренажерів - Мясоєдов, Б. Г. (ХНУРЕ, 2020)
The analysis of existing simulators is carried out in order to determine the object of research, in this case – what measurements are made to determine the results of a shot, what precision of measurements is required, what range of measured values, what are the criteria for evaluating the result of a "shot", etc. real objects and processes are simulated with the help of simulators, in order to understand the principles of work of simulators (models) and their classification it is necessary to start with real objects and processes.
Keywords: тренажер; мішень